Frozen Section Results of The Patients With Pap Class Ii Thyroid Lesions Preopeatively and Have Malignity Suspicion Intraopreatively - Ayten, Refik; Aygen, Erhan (Fırat University, 2003)
Aim: We aimed to investigate the value of frozen section examination that patients with nodular goitre whose diagnosis were benign preoperatively, but suspicion existed in operative theatre. Materials and method: Seventy-six patients with multinodular goitre whose diagnosis were PAP Class II preoperatively and in whom frozen section was performed because of malignancy suspicion, such as firm, fixed nodul with calcification or found lymph node at the operation, were included study. Patients' ages, gender, results of frozen section, type of operations, and histopathologic findings were recorded. Results of frozen section and histopathologic findings were compared. Frozen section specifity and sensitivity were calculated. Results: Sixty-seven of 76 patients (88.1 %) had benign, 9 of 76 (11.9 %) patients had malign thyroideal disease. All 5 patients whose frozen section diagnosis were malign, histopathologic findings were also malign. Four of 71 patients (5.6 %) whose frozen section diagnosis were benign, were found malign in histopathologic examination. Sensitivity and specifity of the frozen section were found 55.5% and 100% respectively, in discrimination of the malign thyroideal disease. Conclusion: In Pap Class II thyroid lesions, if there is some suspicion about malignancy at operation, frozen section investigation is strongly suggested. We conclude that frozen section's specifity is high and can be used safely.

Amaç: Ameliyat öncesinde malignite şüphesi olmayan fakat ameliyat esnasında şüphelenilen hastalarda, yapılan frozen kesit incelemesinin (FKİ) malignite tanısını koymadaki katkısını literatür eşliğinde tartışmayı amaçladık. Gereç ve yöntem: Ameliyat öncesi incelemesinde PAP Class II olan multinodüler guatrlı hastalarda, ameliyat esnasında sert, fikse, kalsifik nodül veya lenf nodu tespit edilerek şüphelenilip FKİ yapılan 76 hasta çalışmaya alındı. Hastaların yaşları, cinsiyetleri, FKİ sonuçları, yapılan ameliyat ve histopatolojik sonuçları irdelendi. FKİ sonuçları histopatolojik sonuçlarla karşılaştırılarak FKİ'nin sensitivite ve spesitiviteleri hesaplandı. Bulgular: Çalışmaya alınan 76 hastanın 67'sinde (%88.1) benign tiroid hastalığı ve 9'unda (%11.9) malign tiroid hastalığı vardı. FKİ sonucu malign olan 5 hastanın hepsinde histopatoloji malign olup, FKİ'si benign olan 71 hastanın 4'ünde (%5.6) histopatoloji malign idi. FKİ'nin tiroid malignitelerini ayırt etmede sensitivitesi %55,5, spesifitesi ise %100 idi. Sonuç: Sonuç olarak ameliyat öncesinde malignite şüphesi olmayan hastalardan ameliyat esnasında şüphelenilmesi halinde FKİ çalışılması gerekir. FKİ tiroid hastalıklarında, maligniteyi ayırmada spesifitesi yüksek olup güvenle kullanılabilir bir yöntem olduğu kanaatindeyiz.
Ameliyat Öncesi Pap Class-II Tiroid Lezyonlarının Ameliyat Esnasında Malignite Şüphesi Olanlarında Frozen Kesit İncelemesinin Sonuçları